Letter : Spanish seamen - Hirst, Stanley
025a-0021-001 Telegraphic Address TRADESUNION SOWEST LONDON Telephones Victoria 7671/5 Transport and General Workers' Union Registered Trade Union No. 18341 Approved Society for National Health Insurance No. 398 Registered Offices Transport House, Smith Square, Westminster, London, S.W.1 General Secretary Ernest Bevin Financial Secretary Stanley Hirst Asst General Secretary Arthur Deakin REF. SH/AWP. 19th Nov. 1940. Sir Walter Citrine, Trades Union Congress, Transport House, S mith Square, S.W.1. Dear Sir Walter, SPANISH SEAMEN. Further to the letter of yesterday's date sent to you by Mr. Deakin, Acting General Secretary of the above Union, I am now enclosing cheque for £280.0.0d., being the Union's quota of the additional grant of £1,000, and shall be pleased to receive your receipt for the amount in due course. Yours faithfully, Stanley Hirst FINANCIAL SECRETARY. ENCLO: CHEQUE. 292/946/25a/21